Ancient volcanism on the Moon: Insights from Pb isotopes in the MIL 13317 and Kalahari 009 lunar meteorites - Snape, J.; Curran, N.; Whitehouse, M.; Nemchin, Alexander; Joy, K.; Hopkinson, T.; Anand, M.; Bellucci, J.; Kenny, G. (Elsevier BV, 2018)
Lunar meteorites provide a potential opportunity to expand the study of ancient (>4000 Ma) basaltic volcanism on the Moon, of which there are only a few examples in the Apollo sample collection. Secondary Ion Mass Spectrometry (SIMS) was used to determine the Pb isotopic compositions of multiple mineral phases (Ca-phosphates, baddeleyite K-feldspar, K-rich glass and plagioclase) in two lunar meteorites, Miller Range (MIL) 13317 and Kalahari (Kal) 009. These data were used to calculate crystallisation ages of 4332±2 Ma (95% confidence level) for basaltic clasts in MIL 13317, and 4369±7 Ma (95% confidence level) for the monomict basaltic breccia Kal 009. From the analyses of the MIL 13317 basaltic clasts, it was possible to determine an initial Pb isotopic composition of the protolith from which the clasts originated, and infer a 238U/204Pb ratio (µ-value) of 850±130 (2s uncertainty) for the magmatic source of this basalt. This is lower than µ-values determined previously for KREEP-rich (an acronym for K, Rare Earth Elements and P) basalts, although analyses of other lithological components in the meteorite suggest the presence of a KREEP component in the regolith from which the breccia was formed and, therefore, a more probable origin for the meteorite on the lunar nearside. It was not possible to determine a similar initial Pb isotopic composition from the Kal 009 data, but previous studies of the meteorite have highlighted the very low concentrations of incompatible trace elements and proposed an origin on the farside of the Moon. Taken together, the data from these two meteorites provide more compelling evidence for widespread ancient volcanism on the Moon. Furthermore, the compositional differences between the basaltic materials in the meteorites provide evidence that this volcanism was not an isolated or localised occurrence, but happened in multiple locations on the Moon and at distinct times. In light of previous studies into early lunar magmatic evolution, these data also imply that basaltic volcanism commenced almost immediately after Lunar Magma Ocean (LMO) crystallisation, as defined by Nd, Hf and Pb model ages at about 4370 Ma.